Modelling Nature-Based Solutions in HEC-RAS - Ramtin Sabeti; Thomas Rodding Kjeldsen; Matt Chambers; Hamed Moftakhari; Luis Partida; Ioanna Stamataki; Solomon Simmonds; Rebecca Lee; Barry Hankin; Melissa Hoskings; Katherine Dixon; James Molloy; et al. (Water Resources Management, 2026)
Nature-based solutions (NBS) are becoming increasingly popular for mitigating flood risk while providing multiple benefits such as enhanced biodiversity, and improved water quality. Hydraulic modelling is an essential tool for evaluating and optimising the flood risk regulating service of NBS. Yet, there is no standardised approach to represent NBS interventions in hydraulic models, leading to inconsistent implementations. This study reports a systematic review of 1,080 publications from Scopus and Web of Science. A final selection of 30 key-studies is identified utilising HEC-RAS to model NBS interventions. By collating and synthesising the various approaches documented in these studies, a consolidated resource for researchers and practitioners is provided. This synthesis offers practical recommendations for the application of different NBS interventions in hydraulic modelling and outlines the corresponding parameter ranges to consider. A critical assessment is undertaken on how these interventions map to specific parameters in the governing hydraulic equations, elucidating the physical mechanisms of flow attenuation and water storage that are broadly applicable to all hydraulic models. To demonstrate the real-world utility of these recommendations, a case study of the River Chew catchment (England) is presented, detailing pre- and post-intervention configurations wherein multiple candidate areas are converted to wetland and woodland using a HEC-RAS 2D model; this section is available in the Supplementary Material. Graphical Abstract